AI-driven Solutions to Detect Bone Issues and Assess Organ Health During Trauma Surgery (Contemporary Journal of Social Science Review, 2024)
This study introduces a blend of imaging and artificial intelligence that is set to revolutionize trauma surgery. By linking up with a knowledge repository, the application establishes connections between identified fractures and existing medical records, recommendations and insights thereby enriching the field. From a standpoint, it represents an advancement in academic research by pushing forward cutting-edge technology in medical diagnostics. This research serves as a tool by speeding up processes through more accurate pinpointing of fractures benefiting policymakers by emphasizing the importance of staying updated and embracing continuous learning networks. In times of trauma decisions on treatment for recovery are crucial. Making mistakes in this regard can lead someone into life-threatening situations. Surgeons are unable to determine the health condition and injuries of the patient without help. Using AI to assess the patient’s well-being results, in diagnoses and customized treatment plans that consider both the fracture and any related organ damage ultimately enhancing recovery. In summary, this current study marks progress, in integrating AI and medical imaging within trauma surgery. The study’s impact, on research, healthcare services, and policy formulation highlights the importance of the research for advancing diagnostics and treatment methods in the future. We achieved 98% accuracy in bone detection and 100% accuracy in abdominal organ detection using a different algorithm than previous works.